2020
DOI: 10.3390/app10228305
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Scattering Models from Rough Surfaces: A Brief Review and Recent Advances

Abstract: This paper proposes a brief review of acoustic wave scattering models from rough surfaces. This review is intended to provide an up-to-date survey of the analytical approximate or semi-analytical methods that are encountered in acoustic scattering from random rough surfaces. Thus, this review focuses only on the scattering of acoustic waves and does not deal with the transmission through a rough interface of waves within a solid material. The main used approximations are classified here into two types: the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 133 publications
0
7
0
Order By: Relevance
“…The set-up is more than the one used in the DPS experiments: both the top surface and blackwall are more indulated and there is a backwall breaking flaw, creating additional response, see Figures 15b and 16a. The numerical experiments conducted with CIVA [22] (a commercial package for analyzing and simulating NDT [23][24][25][26][27][28], in particular, NDT of components with irregular surfaces [7,8,28,29]) showed that the notch fabricated for the purposes of this experiment was best imaged using the half-skip LTT mode, with the L (longitudinal) transmitted signal converting at the backwall to the T (transverse) and then reflecting from the notch, so that the received signal is also T, see Figure 16a. The set-up is more challenging than the one used in the DPS experiments: both the top surface and blackwall are more indulated and there is a backwall breaking flaw, creating additional response, see Figures 15b and 16a.…”
Section: Testing Autonde On Cea Datamentioning
confidence: 99%
“…The set-up is more than the one used in the DPS experiments: both the top surface and blackwall are more indulated and there is a backwall breaking flaw, creating additional response, see Figures 15b and 16a. The numerical experiments conducted with CIVA [22] (a commercial package for analyzing and simulating NDT [23][24][25][26][27][28], in particular, NDT of components with irregular surfaces [7,8,28,29]) showed that the notch fabricated for the purposes of this experiment was best imaged using the half-skip LTT mode, with the L (longitudinal) transmitted signal converting at the backwall to the T (transverse) and then reflecting from the notch, so that the received signal is also T, see Figure 16a. The set-up is more challenging than the one used in the DPS experiments: both the top surface and blackwall are more indulated and there is a backwall breaking flaw, creating additional response, see Figures 15b and 16a.…”
Section: Testing Autonde On Cea Datamentioning
confidence: 99%
“…Other related methods e.g. small slope approximation [8] and parabolic equation [9], are reviewed by more recent authors [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…reflectance), the ratio between the reflected and the incident energy. Since the characterization of scattering is not so simple [2], researches continue to be conducted in order to experimentally evaluate the sound reflection from diffuse surfaces. Recently, investigations on the sound reflection from corrugated diffuse surfaces have been done with a twomicrophone method [3].…”
Section: Introductionmentioning
confidence: 99%